Comparison of the performance of digital variance angiography and digital subtraction angiography in children with arteriovenous malformations: a retrospective observational study - Balázs Bence Nyárády; Renáta Gubán; Ákos Pataki; András Bibok; Zsuzsanna Mihály; Dávid Korda; Dénes Horváthy; Anikó Ilona Nagy; János Pál Kiss; Edit Dósa (European Radiology Experimental)
Abstract Background Reducing contrast agent and radiation exposure is paramount for pediatric patients. Digital variance angiography (DVA) might address this need by increasing the contrast-to-noise ratio (CNR). Materials and methods A total of 132 raw iodinated contrast angiograms of 10 children (mean age: 12 years) who had endovascular procedures for arteriovenous malformations were retrospectively processed for DVA analysis. The CNR of the DVA and digital subtraction angiography (DSA) images was calculated. The visual image quality was assessed using a four-point Likert scale. Statistical analyses were based on the Wilcoxon signed-rank test and one-sample t-test. Results The CNR was determined and compared for 3,318 regions of interest in 132 image pairs in four anatomical regions (upper limb (UL), lower limb (LL), head and neck (HN), and chest (CH)). DVA outperformed DSA, with a median overall CNRDVA/CNRDSA ratio of 2.00 (UL, 1.83; LL, 1.71; HN, 2.06; CH, 2.23; all p < 0.001). The paired Likert scale scores were significantly different from zero in 50% of the comparisons (in all large vessel and small vessel groups, except in the UL region, and the tissue blush group in the LL and HN regions), indicating a superiority of DSA, but the difference was clinically negligible. Conclusion Although DVA improved CNR, it did not surpass DSA in subjective image quality, possibly due to motion artifacts and the high baseline quality of DSA images. Relevance statement The enhanced CNR seen with DVA indicates a potential quality reserve that could be exploited to safely reduce contrast agent dose and radiation risks in pediatric patients, who are more susceptible to the long-term effects of radiation. Key points In previous studies, DVA was superior to DSA due to a higher CNR and better image quality. However, no evidence was available regarding pediatric endovascular procedures. While DVA exhibited a marked advantage in terms of the CNR, it was unable to surpass DSA in terms of visual assessment. The enhanced CNR seen with DVA indicates a potential quality reserve that could be exploited to safely reduce contrast agent dose and radiation risks in pediatric patients. Graphical Abstract